The role of gender in the prevalence of human leptospirosis in Albania - Edmond Puca; Pellumb Pipero; Arjan Harxhi; Erjona Abazaj; Arjet Gega; Entela Puca; Ilir Akshija (Journal of Infection in Developing Countries)
Introduction: Leptospirosis is a zoonotic spirochetal disease with global importance, which continues to have a major impact on public health in developing countries. The prevalence of the disease is much higher in males. The objectives of this study were: to give some data and to share our experience with human leptospirosis in Albania; to describe the prevalence regarding to the role of gender in the prevalence of human leptospirosis; to make a gender specific analysis of the clinical manifestations in patients diagnosed and treated for leptospirosis in our service and to make a review of literature related to this hypothesis.